Mutagenesis of the rpoS gene involved in alteration of outer membrane composition - Rahpeyma, Sayyed Shahryar (Iran J Microbiol, 2019)
BACKGROUND AND OBJECTIVES: rpoS is a bacterial sigma factor of RNA polymerase which is involved in the expression of the genes which control regulons and play a critical role in survival against stresses. Few suitable vectors are available which could be maintained successfully in Flexibacter chinesis cells and could in particular be used as a suicide vector to make mutation in the rpoS gene. The aim of this study was to investigate if rpoS mutagenesis has impact on bacterial morphology in addition to cell division. MATERIALS AND METHODS: A 0.603 kb BamHI-PstI fragment subclone of pICRPOS38Ω was cloned into linearized pLYLO3. The final construct, pLRPOS38 suicide vector, was introduced into Flexibacter chinesis. Then the cytoplasm of mutant strain and wild-type were investigated by transmission electron microscopy. RESULTS: After successful subcloning of suicide vector into F. chinesis, based on TEM study, it was demonstrated that mutation in rpoS gene leads to decomposition of outer membrane of F. chinesis. CONCLUSION: A suitable vector to make suicide mutation in rpoS was constructed for F. chinesi.